Instrumentation of a field hockey stick to detect stick and ball interaction during a drag flick - Jennings, M. J.; Blanchonette, I.; Lucas, S. R.; Morgan, S. W.; Helmer, R. J. N.; Yang, C. (Procedia Engineering, 2010)
The drag flick was introduced to field hockey in the early 1990's by Dutch player Taco Hajo van den Honert. It has become a major offensive weapon as a set play in penalty corners, with skilled drag flickers highly sought after at all levels of the game.This study investigated the forces between ball and stick and the location of the ball on the stick during a drag flick. Force sensors were mounted on the surface of the stick to determine both the forces applied and ball position with high temporal resolution during drag flicking. A high g accelerometer was used to measure the acceleration of the stick head. These devices were synchronised in a common wireless data acquisition system. Three drag flickers with different skill levels were used as subjects and were instructed to direct the ball at a particular target region, a small sector of the field hockey goal.The force sensor data showed that the force and location of the ball during a drag flick was important for controlling drag flicks. The use of the force sensors also affected the friction of the stick surface and made it more difficult for the subjects to impart curvature onto the ball's trajectory consistent with elite competition. Further development of the sensors is required to improve measurement and analysis.